Neonicotinoids, Fipronil, Sulfoxaflor and related Transformation Products in water samples from the Bohai Sea and its surrounding rivers, in summer and fall 2018 - Tanja Naumann; Célia P M Bento; Andreas Wittmann; Juergen Gandrass; Jianhui Tang; Xiaomei Zhen; Lin Liu; Ralf Ebinghaus (PANGAEA, 2022)
Neonicotinoids, fipronil, sulfoxaflor and related transformation products were measured in river- and seawater samples from the Bohai Region, in China. Two sampling campaigns were conducted in 2018 in the Bohai Sea on board of the Chinese research vessel Chuangxin I: one in summer (18-25 August) and one in fall (23 November-14 December). Surface seawater samples were collected at approximately 5 m depth using a SBE991plus CTD (Sea-Bird Scientific, USA). In summer, 47 seawater samples were collected, whereas in fall only 34 sampling stations were possible to be collected due to bad weather conditions. Additionally, another 2 sampling campaigns were conducted in 2018 to 36 major rivers around the Bohai Sea and Northern Yellow Sea, approximately at the same time as the Bohai Sea campaigns, i.e. one in summer (23-30 August) and one in fall (29 October-7 November). The river water sampling stations were located as close as possible to the river mouths while avoiding the influence of salt water. All samples were prepared using an automated solid-phase extraction (SPE), using a LC-Tech FREESTYLE™ XANA workbench (LC Tech GmbH, Germany). Target insecticides were analysed by high performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS). More information can be found in Naumann et al. (2022). The aims of the study were to: 1) investigate the occurrence and spatiotemporal distribution of the target analytes in river- and seawater of the Bohai region, China; 2) perform a fingerprint analysis to identify similarities in contamination patterns between river- and seawater; and 3) to perform an ecological risk assessment to freshwater and marine species based on risk quotients.